Microdamage caused by fatigue loading in human cancellous bone: relationship to reductions in bone biomechanical performance. - Floor M Lambers; Amanda R Bouman; Clare M Rimnac; Christopher J Hernandez (PLoS ONE, 2013)
Vertebral fractures associated with osteoporosis are often the result of tissue damage accumulated over time. Microscopic tissue damage (microdamage) generated in vivo is believed to be a mechanically relevant aspect of bone quality that may contribute to fracture risk. Although the presence of microdamage in bone tissue has been documented, the relationship between loading, microdamage accumulation and mechanical failure is not well understood. The aim of the current study was to determine how microdamage accumulates in human vertebral cancellous bone subjected to cyclic fatigue loading. Cancellous bone cores (n = 32) from the third lumbar vertebra of 16 donors (10 male, 6 female, age 76 ± 8.8, mean ± SD) were subjected to compressive cyclic loading at σ/E0 = 0.0035 (where σ is stress and E0 is the initial Young's modulus). Cyclic loading was suspended before failure at one of seven different amounts of loading and specimens were stained for microdamage using lead uranyl acetate. Damage volume fraction (DV/BV) varied from 0.8 ± 0.5% (no loading) to 3.4 ± 2.1% (fatigue-loaded to complete failure) and was linearly related to the reductions in Young's modulus caused by fatigue loading (r(2) = 0.60, p<0.01). The relationship between reductions in Young's modulus and proportion of fatigue life was nonlinear and suggests that most microdamage generation occurs late in fatigue loading, during the tertiary phase. Our results indicate that human vertebral cancellous bone tissue with a DV/BV of 1.5% is expected to have, on average, a Young's modulus 31% lower than the same tissue without microdamage and is able to withstand 92% fewer cycles before failure than the same tissue without microdamage. Hence, even small amounts of microscopic tissue damage in human vertebral cancellous bone may have large effects on subsequent biomechanical performance.